2017
DOI: 10.1111/pops.12464
|View full text |Cite
|
Sign up to set email alerts
|

In Politics We Trust…or Not? Trusting and Distrusting Demonstrators Compared

Abstract: This article sheds light on the debate regarding political trust and protest activity. The debate boils down to the question whether trust in politics is positively or negatively related to protest activity. We exploit a dataset encompassing data on about 9,000 demonstrators spread over seven European countries. These demonstrators' trust in their parliaments varies widely, ranging from trustworthy capable, to corrupt incapable. We examine the diverging sociodemographic profiles and motivational dynamics that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…To our knowledge, there are two main approaches aimed at exploring people's perceptions of their political context regarding protests from a psychological perspective. The first of them Saavedra & Drury 7 has used measures associated with people's trust in political institutions, politicians, and their representativeness (e.g., Lee & Chan, 2018;Li, Lee, & Li, 2016;van Stekelenburg & Klandermans, 2018), whereas the second has used a validated scale of measurement, subjective political openness repression (SPO-R), to evaluate non-participants' perceptions of the restrictions that both the government and the police impose on protests (see . Thus, employing SPO-R, Saavedra and collaborators (2019) have demonstrated that non-participants may support protesters' violence against the police according to the extent people perceive authorities impose harsh restrictions on protests.…”
Section: The Perceived Political Contextmentioning
confidence: 99%
“…To our knowledge, there are two main approaches aimed at exploring people's perceptions of their political context regarding protests from a psychological perspective. The first of them Saavedra & Drury 7 has used measures associated with people's trust in political institutions, politicians, and their representativeness (e.g., Lee & Chan, 2018;Li, Lee, & Li, 2016;van Stekelenburg & Klandermans, 2018), whereas the second has used a validated scale of measurement, subjective political openness repression (SPO-R), to evaluate non-participants' perceptions of the restrictions that both the government and the police impose on protests (see . Thus, employing SPO-R, Saavedra and collaborators (2019) have demonstrated that non-participants may support protesters' violence against the police according to the extent people perceive authorities impose harsh restrictions on protests.…”
Section: The Perceived Political Contextmentioning
confidence: 99%
“…Even though the proposition that political activism may lead to a loss of institutional trust generally would be acknowledged by students of social movement and political protest, the literature on social movement outcomes, nonetheless, tends to be silent on the issue of activism and its consequences for institutional trust (Bosi, Giugni, Uba ; Giugni, McAdam and Tilly ). Instead, studies of this relationship tend to view institutional trust as a cause generating activism (Ejrnæs ; Hooghe and Marien ; Kaase ; Norris ; van Stekelenburg and Klandermans ). Supplementing this approach, the overall contribution of this paper is to argue that the loss of institutional trust should also be analysed as an outcome of activism.…”
Section: Introductionmentioning
confidence: 99%
“…This means researchers need to test if SPO-R and its dimensions are capable of predicting relevant attitudes (e.g., willingness to take part in protests) or (actual) behaviours in relation to collective action. Furthermore, future research should explore the convergent/divergent validity between SPO-R's dimensions and other constructs that have been used in recent literature to assess the political context where protests take place, such as perceived political cynicism, external efficacy, and political trust (see Lee, 2010;Lee & Chan, 2018;Sabucedo, Gómez-Román, Alzate, van Stekelenburg, & Klandermans, 2017;van Stekelenburg & Klandermans, 2018).…”
Section: Discussionmentioning
confidence: 99%